Egyptian Arabic Broken Plurals in DATR - Winchester, Lindley (My University, 2018)
This paper examines plural inflectional processes in Egyptian Arabic, with specific focus on the complex broken plural system. The data used in this examination is a set of 114 lexemes from a dictionary of the Egyptian Arabic variety by Badawi & Hinds (1986) collected through comparison of singular to plural template correspondences proposed by Gadalla (2000). The theoretical side of this analysis builds upon Alain Kihm’s realizational “Root-and-Site Hypothesis”, which categorizes concatenative and non-concatenative morphological processes as approachable in the same manner when discussing inflection as not only represented in segments but also as “sites” where inflectional operations may take place (Kihm 2006: 69). To organize the data through a computational lens, I emulate Kihm’s approach in DATR, a lexical knowledge representation language, to generate the grammatical forms for a set of both broken and regular plural nouns. The hierarchically-structured inheritance of DATR allows for default templates to be defined and overridden, permitting a wide scope of variation to be represented with little code content. Overall, the analysis reveals that complex morphological phenomena, such as the broken plural, can be accounted for through a combination of theoretical and computational approaches.
Keywords: DATR; Egyptian Arabic; Plural